Cost Volume Profit (CVP) Analysis As A Profit Planning Tool At Lay Cang MSMEs - Mohamad Bastomi; Sudarmiatin Sudarmiatin; Agus Hermawan (Cita Konsultindo Research Center, 2023)
Having a strategic role in aspects of economic growth does not guarantee that MSMEs are able to manage their businesses well. Financial management in a business is an important factor that must be studied and improved in order to improve the quality of business management. In order to obtain optimal profits, business actors need to carry out profit planning related to components that can affect profits, such as costs, sales volume and production. One of the analytical tools used is using cost, volume and profit analysis or commonly referred to as Cost Volume Profit (CVP) analysis. The purpose of this study is to analyse financial management related to cost volume profit at Lay Cang MSMEs. In general, MSMEs do not understand the level of sales that must be maintained so as not to experience losses by taking into account the costs incurred for production. The method used is a descriptive qualitative method with a literature review approach complemented by direct interviews with the managers of Lay Cang MSMEs. Based on the results of research using Cost Volume Profit analysis, information was obtained that the revenue obtained by Lay Cang MSMEs was able to cover variable costs and fixed costs. The application of cost volume profit (CVP) analysis helps Lay Cang MSMEs in estimating the maximum profit and knowing how many units of total sales and revenue must be obtained in order to reach the Break Event Point.